Primer on the autonomic nervous system - Biaggioni, I. (Italo); Browning, Kirsteen; Fink, Gregory; Jordan, Jens; Low, Phillip A.; Paton, Julian F. R. (Academic Press, an imprint of Elsevier, 2023)
Primer on the Autonomic Nervous System, Fourth Edition provides a concise and accessible overview of autonomic neuroscience for students, scientists, and clinicians. The book's 142 chapters draw on the expertise of more than 215 basic scientists and clinicians who discuss key information on how the autonomic nervous system controls the body, particularly in response to stress. This new edition also focuses on the translational crossover between basic and clinical research. In addition to comprehensively covering all aspects of autonomic physiology and pathology, topics such as psychopharmacology decoding and modulating nerve function are also explored.